The effect of supplemental dietary chromium on performance, some blood parameters and tissue chromium contents of rabbits - Şahin, Kazım; Şahin, Nurhan; Güler, T; Ertas, ON (Scientific Technical Research Council Turkey, 2001)
The aim of the present study was to evaluate the effect of supplemental dietary chromium (Cr) on average daily gain, feed intake, feed efficiency and several serum constituents and tissue chromium contents of pregnant does, newborns and weaned growing rabbits. At the beginning of the study, 36 rabbits were randomly divided into three treatment groups as follows: 0, 200 and 400 ppb. Supplemental chromium was provided by Cr chloride incorporated into a basal diet containing 539.17 ppb Cr. Blood and tissue were collected at the end of study and analyzed for serum glutamic oxalate transaminase (SGOT), serum glutamic pyruvate transaminase (SGPT), Ca, P. Na, K, total immunoglobulins and tissue Cr contents. Supplemental Cr had no effects (P>0.05) on average daily gain, feed intake or feed efficiency of the weaned rabbits. Supplemental Cr also did not affect (P>0.05) serum total cholesterol, SGOT, SGPT, Ca, P, Na, K, or tissue Cr contents in any rabbit types. However, supplemental Cr increased (P<0.05) total serum immunoglobulin levels in all rabbits. The results of this investigation indicate that supplemental Cr had no effect on performance, serum contituents or Cr content in various tissues, but increased total serum immunoglobulin.
Keywords: chromium; performance; cholesterol; SCOT; SGPT; Ca; P; Na; K; immunoglobulins; tissue; rabbits